Constitutional process and National Assembly of 1991. Representations of peace in the written press from Voz. La verdad del pueblo (Voice. The truth of the people) - Echeverry Campuzano, Ángela Milena; Ramírez Bacca, Renzo (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
The article analyzes the representations identified during the peace process and constitutional reform the National Constituent Assembly (ANC) in Colombia 1991. It takes into account previous interdisciplinary studies that address the issues, and the categories as Representation, Peace and Constitutional Process. The central questions are: Why the Assembly created expectations of peace and changes in Colombia?, and What were their representations in the written press ? The legal background and socio-political context show government and university initiatives for constitutional reform, but also some efforts towards peace talks between the Government and the CGSB during the administrations of President Virgilio Barco Vargas (1986 - 1990) and Cesar Augusto Gaviria Trujillo (1990-1994). The case chosen for analysis are the speeches and messages posted on the weekly Voz. La verdad del pueblo, which are oriented to represent: 1) the constitutional reforms of the ANC as generators peace and, 2) the Assembly as a mediator, companion, or driver of the peace process between the government and the CGSB (CGSB). The authors argue how the proposed constitutional change was not necessarily the mechanism that ensured peace between the State and armed insurgent groups through the National Constituent Assembly; but it was representing the most peace speeches held in the Colombian society of the time.